Macrobending Multimode Plastic Optical Fiber Coated with PANI-PVA composite as a pH sensor: Ali Yunus Rohedi, Rizqi Nur Ainun, Iim Fatimah, Nurrisma Puspitasari, S Sudarsono, Gatut Yudoyono - Ali Yunus Rohedi Ali Yunus Rohedi; Rizqi Nur Ainun Rizqi Nur Ainun; Iim Fatimah Iim Fatimah; Nurrisma Puspitasari Nurrisma Puspitasari; Sudarsono Sudarsono; Gatut Yudoyono Gatut Yudoyono (Jurnal Fisika dan Aplikasinya, 2024)
The pH measurement is essential in medicine, industry, and research, and each requires measuring instruments with different sensitivities. Measuring the pH of a solution, in principle, measures hydrogen ions in the solution. In this study, a pH sensor was designed and fabricated using macrobending multimode optical fiber. The optical fiber cladding was peeled off and replaced with a PANI-PVA (polyaniline-polyvinyl alcohol) composite layer, bent with a 2.0 and 2.5 cm diameter. The results showed that the pH sensor could measure the solution's pH linearly in the range of pH = 2 to 8.